GMAT for Dummies 2021: Book + 7 Practice Tests Online + Flashcards - Lisa Zimmer Hatch; Scott A. Hatch (John Wiley & Sons, Inc., 2021)
You have your heart set on getting into a particular MBA program, but you're required to submit your GMAT score as part of the application process. Ack! If you dread the idea of taking a standardized test, you've come to the right place. GMAT For Dummies 2021 with Online Practice gets you ready for test day with helpful reviews and smart advice. To make the chore of studying a bit more bearable, the four parts of the test are broken down into sections so you can focus on exactly what you need. If you need a refresher on grammar and reading comprehension, it's here. Is math your nemesis? Overcome the challenge with reviews of algebra, geometry, and statistics. And the exasperating but essential topics of essay writing and integrated reasoning are covered too. In addition, you get insights into how to avoid GMAT pitfalls and make the most of time-management tactics during the exam. Take a pre-assessment test to identify the subject areas you need to brush up on Access 7 practice tests and 500 flashcards online Hone your analytical and reasoning skills Create a targeted study plan If you want to conquer the GMAT and stand out from other MBA program applicants, you'll find everything you need here for a stellar score!
Keywords: Language; Nonfiction